Web crippling study of rivet fastened rectangular hollow flange channel beams with flanges fastened to supports. Issue 7 (July 2017) - Steau, Edward; Keerthan, Poologanathan; Mahendran, Mahen
Thin-walled steel hollow flange channel beams are commonly used as joists and bearers in various flooring systems in buildings. A new rivet fastened rectangular hollow flange channel beam was proposed using an intermittently rivet fastening process as an alternative to welded beams. This flexible fastening process allows rectangular hollow flange channel beams to have greater section optimisation, by configuring web and flange widths and thicknesses. In the industrial applications of rectangular hollow flange channel beams as flooring, roofing or modular building systems, their flanges will be fastened to supports, which will provide increased capacities. However, no research has been conducted to investigate the web crippling capacities of rectangular hollow flange channel beams with flanges fastened to supports under two-flange load cases. Therefore, an experimental study was conducted to investigate the web crippling behaviour and capacities of rectangular hollow flange channel beams based on the new American Iron and Steel Institute S909 standard test method. The web crippling capacities were compared with the predictions from the design equations in Australia/New Zealand Standard 4600 and American Iron and Steel Institute S100 to determine their accuracy in predicting the web crippling capacities of rectangular hollow flange channel beams. Test results showed that these design equations are considerably conservative for the end two-flange load case while being unconservative for the interior two-flange load case. New equations are proposed to determine the web crippling capacities of rectangular hollow flange channel beams with flanges fastened to supports. Test results showed that web crippling capacities increased by 78% and 65% on average for the end two-flange and interior two-flange load cases when flanges were fastened to supports. This article presents the details of this web crippling experimental study of rectangular hollow flange channel beam sections and the results.